Legal and Contractual Framework in Supply Chain Management and Distribution Channels: An Indonesian Perspective - Evita Isretno Israhadi (International Journal of Supply Chain Management, 2018)
The subject matter of this paper concerns the Legal and contractual framework in supply chain management and distribution channels in the Indonesian perspective. A questionnaire survey was carried out with regulatory dimensions and such criteria that will enable the researcher to get information on legal and contractual framework in supply chain companies of various sectors such as coal, cement, construction, timber, and agriculture in Indonesia. A theoretical sustainable SCM model was devised to carry out this empirical study. The data collected was examined through content analysis approach. The findings revealed the absence of a formal and written legal and conceptual framework in the sampled organizations. These findings are expected to help supply chain managers and stakeholders in various industry sectors to in Indonesia to design such legal and contractual frameworks for supply chain management and distribution networks that would help Indonesian businesses operate smoothly.